Teachers' Evaluation of the Pedagogical Activity of Teaching Assistants in a Kindergarten - Radmila Burkovičová (Charles University, 2021)
The article presents results on identifying activities required from teaching assistants in kindergartens by legislative documents and their implementation and evaluation. The respondents were 32 qualified female teachers and 32 teaching assistants from the same kindergarten classes. The implementation of activities was evaluated by the teachers in 2017-2019. Methods: Qualitative content analysis of legislative documents, interviews identifying activities performed by teaching assistants, and teachers' evaluation. Results: In direct pedagogical activities, assistants' help in children's physical activation, adaptation to the kindergarten environment, strengthening of basic habits, protecting safety and health, and group activities according to teachers' established procedures and instructions focused on the children's SEN were evaluated as positive. Failure to provide support and assistance to children with SEN, excessive performance of some activities, and inappropriate criticism were seen as negative. In activities related to direct pedagogical activities, care and concern for intact children were evaluated as positive. Failure to assist children and mutual conflicts of assistants in front of children were evaluated as unacceptable. Their knowledge of children's diagnostic results was evaluated as being insufficient. The teachers also stated their desires and, expectations regarding the implementation of some activities. Conclusion: The results of the evaluation of the implementation of the teaching assistants' activity in kindergartens provides an area for their improvement.